A new instrument to describe indicators of well-being in old-old patients with severe dementia--the Vienna List - Porzsolt, Franz; Kojer, Marina; Schmidl, Martina; Greimel, Elfriede R; Sigle, Jörg; Richter, Joerg; Eisemann, Martin (Health and quality of life outcomes, 2004)
In patients with very severe dementia self-rating of quality of life usually is not possible and appropriate instruments for proxy-ratings are not available. The aim of this project is to develop an instrument of clinical proxy-ratings for this population. Using electronic instruments, physicians and nurses recorded patient behaviour and changes of behaviour over a period of one year. Based on these data a list of 65 items was generated and subsequently allocated to 14 categories. This list was tested in 217 patients (61-105 yrs) with dementia diagnosed according to ICD-10 by both physicians and nurses. The severity of dementia was assessed by means of the Global Deterioration Scale (GDS) and the Brief Cognitive Rating Scale (BCRS). The Spitzer-Index (proxy-rating) was used as a global quality of life measure. Activity of daily living was rated using the Barthel Index. A factor analysis of the original 65 items revealed 5 factors (communication, negative affect, bodily contact, aggression, and mobility). By stepwise removing items we obtained satisfactory internal consistencies of the factors both for nurses' and physicians' ratings. The factors were generally unrelated. The validity of the instrument was proven by correlations of the factors communication and mobility with the Brief Cognitive Rating Scale (BCRS) and the Barthel-Index. The results demonstrate the reliability and validity of the Vienna List as a proxy rating measurement of quality of life in patients with severe dementia. The psychometric properties of the scale have to be proved in further studies.